Life insurance companies' performance and intellectual capital: A long-term perspective - Kweh Q.L.; Lu W.-M.; Wang W.-K.; Su M.-H. (World Scientific Publishing Co. Pte Ltd, 2023)
This study used dynamic data envelopment analysis (dynamic DEA) to evaluate the operating performance of life insurance companies in Taiwan and China. In addition, this study adopted panel data regression, which employs the cross-section and time-series approaches, to investigate the impact of intellectual capital (IC) on operating performance. The results indicated that the overall performance of life insurance companies in China was better than that of life insurance companies in Taiwan. Furthermore, in both countries, the performance of life insurance companies with local capital was better than that of companies with foreign capital. The results also showed that human capital (HC) and structural capital (SC) had impacts on the operating performance of life insurance companies. The potential applications and strengths of DEA in assessing the life insurance industries in Taiwan and China are highlighted. © 2014 World Scientific Publishing Company.